2011
DOI: 10.1039/c1ee02349g
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline ionomer with tuneable water uptakes for electrochemical energy technologies

Abstract: A simple aqueous-processable alkaline ionomer (amenable to scale-up) has been developed for enhancing electrode/electrolyte interfaces in clean energy devices (e.g. alkaline polymer electrolyte membrane fuel cells). The water 10 uptake of the alkaline ionomer is tuneable allowing its use as a tool for fundamental studies into these interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…1) in the QA formed by DABCO and -CH 2 Cl (the intensity of the N atom marked 10 was very low), and the peak at 399.4 eV can only be attributed to the N atom in the unreacted tertiary amine of DABCO (marked 11 in Fig. 1) [6,52]. Furthermore, the area ratio of the above two peaks was 48:52, close to 1:1, which confirmed that only one N atom in the DABCO was reacted (a trace amount of crosslinking on DABCO cannot be excluded).…”
Section: Performance Evaluation Of Pbi-c-pvbc/oh Membranementioning
confidence: 97%
“…1) in the QA formed by DABCO and -CH 2 Cl (the intensity of the N atom marked 10 was very low), and the peak at 399.4 eV can only be attributed to the N atom in the unreacted tertiary amine of DABCO (marked 11 in Fig. 1) [6,52]. Furthermore, the area ratio of the above two peaks was 48:52, close to 1:1, which confirmed that only one N atom in the DABCO was reacted (a trace amount of crosslinking on DABCO cannot be excluded).…”
Section: Performance Evaluation Of Pbi-c-pvbc/oh Membranementioning
confidence: 97%
“…At least three aspects have been studied in AEMFCs, including new AEMs with high performances 21–28, advanced ionomers used as binders in AEMFCs 29–34 and novel catalyst systems matched AEMFCs 35–40. Among them, the studies of AEMs should be placed at high priority because AEMs are the core of AEMFCs and can provide fundamental platforms for the studies of binders and catalysts in AEMFCs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the higher concentration of the unoccupied surface catalytic sites for HOR in FC-#5 than that of FC-3# may be another reason for the grater P max of FC-#5. It was suggested previously that the occupation of anodic catalyst surface by the electro-generated water is probably one of the main causes leading to the low AEMFC performance [33]. Therefore, the water should be removed effectively in order to guarantee the smooth oxidation of hydrogen.…”
Section: H 2 /O 2 Fuel Cell Performancementioning
confidence: 99%